Using Translation Memory to Speed up Translation Process - Brkić, Marija (Array, 2009)
Translation process is one aspect of human creativity. Due to globalization, EU accession negotiations, and the need for information exchange, the amount of translation work increases on a daily basis. The translation process is hindered by the fact that the languages involved differ culturally, stylistically, syntactically and lexically. This paper explores the benefits and limitations of TMs (translation memories). TMs are not used for replacing humans in the translation process, but rather for enhancing the human translation process. In this paper, a detailed analysis of Atril’s Déjà Vu X system is presented, along with its time-saving implications, which are based on the reuse of previously stored segments. Excerpts from three different digital camera user manuals are translated from English into Croatian. Evaluation is performed by measuring the time difference between human and TM-based translation speeds in preparation, translation, and revision phases, and with regard to six different parameters.